Effectiveness of Intralesional Triamcinolone Acetonide in the treatment of Chalazion - Asif Aqbal, Ibrar Hussain, Mohammad Zeehan Tahir, Mubashir Rehman, Imran Ahmad. (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the effectiveness of intralesional injection of Triamcinolone acetonide in the treatment of chalazion. Material and Methods: All patients meeting the inclusion criteria were included in the study through OPD. Chalazion was diagnosed on the basis of presence of painless and non tender nodule in the eye lid with size of between 2 mm to 11 mm. Under strict aseptic technique 0.1 to 0.2 ml of triamcinolone acetonide (40 mg/ml) was injected intralesionally by an expert ophthalmologist. Follow up visit was done at two weeks to determine effectiveness in term of reduction in size of chalazion by 2 mm. Results: The mean pre-operative size of chalazion among all patients was 5.1 ± 2.1 mm. At 2 weeks follow up, the successful results (reduction in at least 2 mm size of chalazion from pre-operative size) of intralesional triamcinolone injection were achieved in 92% of patients with 95% in females and 96% in males. Conclusion: Intralesional injection of Triamcinolone acetonide is highly effective in the treatment of chalazion with size between 2 mm to 11 mm with high effectiveness rates in sizes less than 6 mm. Key Words: Chalazion Intralesional Triamcinolone Meibomian gland.